The Effectiveness of a Training Program Based on The Use of Resistance to Sand Frictions on The Improvement of Some Physical and Skill Variables Among Roman Wrestling Players - Assistant Lecturer, Samer Mahdi Saleh (Global Scientific Publishing, 2024)
The objective of the study was to determine the efficacy of a training program utilizing sand friction resistance in enhancing several physical and skill variables in Romanian wrestling athletes. The study introduced a theoretical structure that encompassed sports training, sand training, physical performance, and skill performance. The study utilized the experimental methodology. The research equipment comprised a racemeter, a stopwatch, a measuring tape, measuring ropes, rubber ropes, weighted medicine balls, iron bars, hurdles, wrestling bars, jump ropes, weight jackets, iron hurdles, and a test involving running, pulling up, bridging, and response speed. A sample of (20) Romanian wrestling players under the age of (17) in the Minya Governorate clubs were subjected to the action of broad jump. The participants were placed into two groups: an experimental sample consisting of 10 players, and a control sample consisting of 10 players from the Military Institution Club in Minya. The research findings verified that implementing a sand resistance training program effectively enhances the physical and skill attributes of Romanian wrestling players. The research suggests prioritizing structured training programs for wrestling players, since these programs have been found to enhance both the physical and skill aspects of the sport. Implementing such programs is crucial for elevating the performance level of players.
Keywords: Implementing; crucial; performance